SLC transporters: structure, function, and drug discovery. Issue 6 (18th April 2016) - Colas, Claire; Ung, Peter Man-Un; Schlessinger, Avner
Abstract : The human solute carrier (SLC) transporters are important targets for drug development. Abstract : The human solute carrier (SLC) transporters are important targets for drug development. Structure-based drug discovery for SLC transporters requires the description of their structure, dynamics, and mechanism of interaction with small molecule ligands and ions. The recent determination of atomic structures of human SLC transporters and their homologs, combined with improved computational power and prediction methods, has led to an increased applicability of structure-based drug design methods for human SLC members. In this review, we provide an overview of the SLC transporters' structures and transport mechanisms. We then describe computational techniques, such as homology modeling and virtual screening that are emerging as key tools to discover chemical probes for human SLC members. We illustrate the utility of these methods by presenting case studies in which rational integration of computation and experiment was used to characterize SLC members that transport key nutrients and metabolites, including the amino acid transporters LAT-1 and ASCT2, the SLC13 family of citric acid cycle intermediates transporters, and the glucose transporter GLUT1. We conclude with a brief discussion about future directions in structure-based drug discovery for the human SLC superfamily, one of the most structurally and functionally diverse protein families in human.